Problem Structuring: On the Nature of, and Reaching Agreement About, Goals - Eden, C.; Ackermann, Fran (Springer Berlin Heidelberg, 2013)
In this paper, we raise issues about discovering and modelling purpose that, in our view, can often be missed within operational research practice. We suggest that, in problem solving, there is a danger of taking too little account of: the differences between espoused goals and goals-in-use; the potentially misleading nature of published goals; goals that express the need to avoid outcomes—‘negative goals’; the meaning of goals in an action context rather than the semantics of goal statements; the dynamics and clarity implied by goal relationships; the potential that derives from multi-organisational settings where goals that express an outcome that can only be achieved collaboratively; stakeholder responses to expressed goals—that good solutions can be sabotaged by others; the fact that some goals are contextually important but not a focus for problem solving because they are ‘not-our-core-goals’; and the need to design ambiguity of purpose in expressing goals systems. These issues are illustrated through a number of real case examples drawn from engineering, Police, NHS, a Research Institute, and a Utility company/Regulator setting.